Therapeutic Advancements in Multiple Myeloma - Gozzetti, Alessandro (Frontiers Media S.A., 2014)
Multiple myeloma survival has significantly improved in the latest years due to a broad spectrum of novel agents available for treatment. The introduction of thalidomide, bortezomib, and lenalidomide together with autologous stem-cell transplantation has considerably increased complete remission rate and progression-free survival resulting ultimately in prolonged survival in myeloma patients. Moreover, novel strategies of treatment such as consolidation and maintenance are being used to further implement responses. Finally, a number of new drugs such as carfilzomib and pomalidomide are already in clinical practice, making the future of myeloma patients brighter.